2020
DOI: 10.1177/1461444820924619
|View full text |Cite
|
Sign up to set email alerts
|

Chilling effects and the stock market response to the Snowden revelations

Abstract: This study analyzes the changes in individuals’ Internet search behavior and economic variables following Edward Snowden’s revelation of National Security Agency (NSA) surveillance activities of global Internet communications. We refer to the abrupt changes in individual search behavior beginning in June 2013 following Snowden’s revelations as the “Snowden effect.” The “Snowden effect” is a form of chilling effect. Using data from a unique search engine, DuckDuckGo, we show that chilling effects indeed exist. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Since 2014, there has been an evident decrease in Tor usage after an increase in 2013. This is probably related to a steep increase in users due to Snowden’s 2013 disclosure, which had a “chilling effect” (Rosso et al, 2020), and then the number of users declined to a relatively stable level (Hampson and Jardine, 2017). The trend of Google searches for “Tor”-related knowledge is consistent with the trends of Tor usage.…”
Section: Resultsmentioning
confidence: 99%
“…Since 2014, there has been an evident decrease in Tor usage after an increase in 2013. This is probably related to a steep increase in users due to Snowden’s 2013 disclosure, which had a “chilling effect” (Rosso et al, 2020), and then the number of users declined to a relatively stable level (Hampson and Jardine, 2017). The trend of Google searches for “Tor”-related knowledge is consistent with the trends of Tor usage.…”
Section: Resultsmentioning
confidence: 99%
“…Atheism, Herpes, White Power). Also at the aggregate level of search volume, Rosso et al (2020) found a significant and lasting increase in the use of the DuckDuckGo search engine (whose unique value proposition is to not profile its users) directly following the NSA revelations.…”
Section: Toward An Empirical Test Of Chilling Effectsmentioning
confidence: 99%
“…The nature and scope of digital transformation is becoming an ethical concern of nations under the digital sovereignty 35 rubric. There is no less a concern at an individual level for self-sovereignty 36 in the face of overreach by national authorities 37 , and other private organizations 38 .…”
Section: Ethical Challenges In Technology Adoptionmentioning
confidence: 99%